2020
DOI: 10.2147/dmso.s254537
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hypertension and Its Associated Factors Among Type 2 Diabetes Mellitus Patients at Debre Tabor General Hospital, Northwest Ethiopia</p>

Abstract: Background: Type 2 diabetes mellitus (T2DM) is associated with a high risk of early mortality and morbidity from hypertension. Even though Ethiopia is Africa's first country among the top five in the prevalence of DM, there is a paucity of data on hypertension and its associated factors among patients with type 2 diabetes mellitus. Therefore, this study aimed to determine the prevalence and associated factors of hypertension among type 2 diabetes mellitus patients at Debre Tabor General Hospital, 2019. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
58
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 67 publications
11
58
4
3
Order By: Relevance
“…The findings revealed that among women in rural communities, there is a significant relationship between diabetic status and hypertension, with the odds of hypertension being higher with diabetic participants. This is in agreement with the previous study, as they reported that the odds of hypertension are high with a longer duration of type 2 diabetes mellitus (T2DM) [ 35 ]. Women in the semi-urban area with a family history of heart failure were at high risk of hypertension.…”
Section: Discussionsupporting
confidence: 94%
“…The findings revealed that among women in rural communities, there is a significant relationship between diabetic status and hypertension, with the odds of hypertension being higher with diabetic participants. This is in agreement with the previous study, as they reported that the odds of hypertension are high with a longer duration of type 2 diabetes mellitus (T2DM) [ 35 ]. Women in the semi-urban area with a family history of heart failure were at high risk of hypertension.…”
Section: Discussionsupporting
confidence: 94%
“…A similar prevalence (47.7%) of hypertension in patients with DM was reported in Khartoum, the capital of Sudan [ 22 ]. The prevalence of hypertension among patients with DM in our study (45.6%) was slightly lower than among DM patients in Nigeria (54.2%) [ 10 ] and Ethiopia (59.5%) [ 20 ], and it was much lower than among DM patients in Cameroon (86.2%) [ 21 ]. The association of hypertension and DM could be explained by hyperglycemia, insulin resistance, and dyslipidemia, which promote the atherosclerosis process [ 28 ].…”
Section: Discussionmentioning
confidence: 55%
“…High prevalence of hypertension (~ 25%) [ 16 – 18 ] and DM (20.8%) [ 19 ] has been reported in different parts of Sudan. Previous studies have shown different rates of hypertension among patients with DM in different African settings [ 10 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 21 studies, 5 were from South Africa(42)(43)(44)(45)(46), 5 from Ethiopia(11,(47)(48)(49)(50), 3 from Kenya (51-53), 2 from Tanzania (54, 55), 2 from Nigeria (56, 57), and 1 from Cameron (58), Uganda (59), Botswana(60), and Ghana(61). All studies were institution based cross-sectional studies.…”
mentioning
confidence: 99%
“…All studies were institution based cross-sectional studies. To de ne poor blood pressure control, BP cut point of ≥140/90 was used by 11 studies(11,43,47,48,50,53,(62)(63)(64)(65)(66), ≥140/80 by 3 studies(45,59,67) and ≥130/80 by 7 studies (44, 52, 54-56, 58) (Table 1).…”
mentioning
confidence: 99%